Innovative Legal Modeling for Interdisciplinary Studies on Law and Economic Behavior - Isman, I; Muttaqin, Ahmad Zainul (Indonesian Journal of Islamic Economic Law, 2024)
This study introduces a new paradigm for interdisciplinary empirical legal research by presenting a groundbreaking perspective on the integration and interconnectedness of law and economics. Our research argues for the necessity of this shift. The conventional pragmatic paradigm, which risks fragmenting concepts and methods by reducing meaning to mere data and facts, is eschewed in favor of an integrationinterconnection theory. This paper investigates the theoretical foundations of the proposed paradigm through library research and philosophical inquiry. Our research uncovers two distinct approaches within the new empirical legal studies paradigm. Firstly, the historical approach requires a restructuring of the theory, leading to multidimensional and holistic models. Secondly, the philosophyasasystem approach necessitates method restructuring by utilizing cognitive, holistic, open, and purposeful models. The integration aspect of the paradigm necessitates a comprehensive theoretical restructuring, while the interconnection aspect requires a broadened viewpoint. The historical approach is demonstrated by historical reformation, which encompasses multidimensional and holistic models. In contrast, the philosophyasasystem approach entails methodical reforms through the incorporation of models that focus on cognition, wholeness, openness, and purposefulness. The historical and methodical restructuring prototypes can be seen in the Integrative Legal Theory Model and the Critical Legal Functionalism Model. Our study highlights the significance of incorporating economic behavior into the interdisciplinary framework of empirical legal studies. This will enable a more comprehensive understanding of the complex connections between law and economic dynamics.